Elvira Sastre’s Translation of ’milk and honey’ (2015) by rupi kaur into Spanish: Considerations on Feminism and Ethos - Ferrero, Sabrina Solange (Vertimo studijos, 2023)
This article focuses on Elvira Sastre’s Spanish translation of milk and honey (2015), a collection of poetry by the Indo-Canadian (Insta)poet, rupi kaur1. Our exploration is based on insights from various critics who have recognized the feminist force of kaur’s English original (Deka 2020). Approaching these verses through a gynocritical lens, we draw upon the perspectives of Tanvir Islam (2020) and the insights provided by Tarigan et al. (2021). Guided by a transnational feminist framework of translation (Castro and Spoturno 2020), our analysis extends to the examination of the ethos (Amossy 2010) associated with the enunciative subject responsible for the Spanish rendition, titled otras maneras de usar la boca (2017). Our investigation uncovers that while the translator’s ethos may be characterized as feminist based on the analysis of the prior ethos, the translated text unveils aspects of discursive modalities that challenge this characterization.